We are Proud Boys : how a right-wing street gang ushered in a new era of American extremism - Campbell, Andy (Journalist) (Hachette Books, Hachette Book Group, 2022)
"After the 2016 election, Americans witnessed a frightening trend: the sudden rise of a host of new extremist groups around the country. Empowered by a new president, they started showing up at political rallies, building fervent online presences, and expanding at an alarming rate. Amid all this, one group seemed to show up in the news constantly, creating a reputation for its bizarre behavior and regular violence: the Proud Boys. From acclaimed extremism reporter Andy Campbell, WE ARE PROUD BOYS is the definitive history of this notorious group and all the far-right movements they're connected to. Through groundbreaking new reporting, Campbell delivers the untold story of a gang of bumbling, punch-happy bigots who, under the leadership of a coke-addled media executive in New York, grew to become the centerpiece of American extremism and positioned themselves as the unofficial enforcement arm of the GOP. Beginning with their founding by Gavin McInnes, the media personality best known for co-founding Vice, Campbell takes us deep inside the Proud Boys, laying bare their origins and their rise to prominence, along the way exposing the group's noxious culture and strange rituals. Their bizarre, frightening story lays bare the playbook they have created for all extremist groups to follow going forward, giving Americans the necessary insight to push back against these groups. The story of the Proud Boys is far more than a relic of the Trump era. In Campbell's hands, it is an urgent warning about extremism encroaching into mainstream politics. It is also a window into the dark corners of the internet, where radical and violent factions incubate, and where misogyny and racism thrive. It's an exploration of the web of extremism that includes QAnon conspiracy theory, white nationalists, gun-toting militias, neo-Nazis, incels, and online reactionaries, with the Proud Boys sitting directly in the center. It's an exclusive look at the fascist underbelly of American government today, where top-level Republican politicians count racist street thugs as their personal bodyguards. The Proud Boys were an inevitable symptom of an authoritarian regime, and though their wild story may be unique to this political moment, it won't be the last of its kind"--